Testing the bottom-up hypothesis for the decline in size of anchovy and sardine across European waters through a bioenergetic modeling approach. (January 2023) - Menu, Clara; Pecquerie, Laure; Bacher, Cedric; Doray, Mathieu; Hattab, Tarek; van der Kooij, Jeroen; Huret, Martin
Highlights: The decreasing trend in size continues for European anchovy and sardine. We modeled the impact of temperature and zooplankton on growth variability. Most of the variability in size was explained by regional environments. Trends in the modeled environment were not sufficient to explain the decrease in size. We further explored the effect of a potential decrease in food quality. Abstract: Small pelagic fish have shown a general decrease in size and body condition over the past two decades in several European regional seas. Although the underlying processes are still not well understood, recent studies point to a bottom-up control. In order to better understand how the environment impacts the main individual life history traits, which themselves control the dynamic of the population, we developed a comparative approach between two species, European anchovy and sardine, and across three regions of the Northeast Atlantic and Mediterranean Sea: the English Channel in the north, to the Bay of Biscay and the Gulf of Lion in the south. We developed a bioenergetic modeling framework based on the Dynamic Energy Budget theory (DEB). Our DEB models were forced using two different representations of the lower trophic levels, POLCOMS-ERSEM and SEAPODYM models. Our models were calibrated for the Bay of Biscay and then projected on to the other regions, over the early 2000s (period with bigger fish) and the early 2010s (period with smaller fish). The environment alone, temperature and zooplankton, explained a significant part of the observed regional differences in growth. However, the temporal trends simulated by the lower trophic levels models, when transcribed through bioenergetics, could not explain the strong decrease in length and weight that occurred in the Bay of Biscay (-30 % in weight for anchovy and −20 % for sardine) and in the Gulf of Lion (-30 % for anchovy and −50 % for sardine). Through a scenario approach, we estimated that a decrease in zooplankton quality could be a significant driver of the observed decrease in size both in the Bay of Biscay and in the Gulf of Lion (decrease in assimilable energy of 4 to 5 % and 15 to 17 % in the Bay of Biscay and the Gulf of Lion, respectively). For such a decrease in size, a zooplankton biomass of the same quality should have been reduced by between 17 and 31 % in the Bay of Biscay over a 10- to 15-year period, while no biologically realistic estimations were obtained for the Gulf of Lion. The validity of these proposed changes in biomass and quality is discussed in context of alternative explanations.